Protective effects of thiamine on Wickerhamomyces anomalus against ethanol stress - Li, Yinfeng; Long, Hua; Jiang, Guilan; Yu, Zhihai; Huang, Mingzheng; Zou, Shiping; Guan, Tianbing; Zhao, Yan; Liu, Xiaozhu (Frontiers in Microbiology, 2022)
Wickerhamomyces anomalus (W. anomalus) is widely reported in the brewing industry and has positive effects on the aromatic profiles of wines because of its unique physiological characteristics and metabolic features. However, the accumulation of ethanol during fermentation inhibits the growth of W. anomalus. Thiamine is involved in the response against various abiotic stresses in microorganisms. Therefore, we used transcriptomic and metabolomic analyses to study the effect of thiamine on ethanol-stressed W. anomalus. The results indicate that thiamine could alleviate the inhibitory effect of ethanol stress on the survival of W. anomalus. Differentially expressed genes (DEGs) and differentially expressed metabolites (DEMs) caused by the thiamine intervention were identified as oxidative phosphorylation through integrated transcriptomic and metabolomic analyses. In addition, ethanol treatment decreased the content of intracellular ATP, while thiamine partially alleviated this phenomenon. The present comprehensive transcriptional overview and metabolomic analysis provide insights about the mechanisms of thiamine protection on W. anomalus under ethanol stress and promote the potential applications of W. anomalus in the fermentation industry.